Management and outcomes of spontaneous coronary artery dissection: a systematic review of the literature - Petrović, Milovan; Miljković, Tatjana; Ilić, Aleksandra; Kovačević, Mila; Čanković, Milenko; Dabović, Dragana; Stojšić Milosavljević, Anastazija; Čemerlić Maksimović, Snežana; Jaraković, Milana; Andrić, Dragica; Golubović, Miodrag; Bjelobrk, Marija; et al. (Frontiers in Cardiovascular Medicine, 2024)
Background Contemporary management of spontaneous coronary artery dissection (SCAD) is still controversial. This systematic review of the literature aims to explore outcomes in the patients treated with conservative management vs. invasive strategy. Methods The PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines were followed when we extensively searched three electronic databases: PubMed, ScienceDirect, and Web of Science, for studies that compared conservative vs. invasive revascularization treatment outcomes for patients with SCAD from 2003 to 2023. The outcomes of interest were all-cause death and major adverse cardiovascular events (MACE), including acute coronary syndrome (ACS), heart failure (HF), need for additional revascularization, target vessel revascularization (TVR), SCAD recurrence, and stroke. Results The systematic review included 13 observational studies evaluating 1,801 patients with SCAD. The overall mean age was 49.12 +/− 3.41, and 88% were females. The overall prevalence of arterial hypertension was 33.2%, hyperlipidemia, 26.9%, smoking, 17.8%, and diabetes, 3.9%. Approximately 48.5% of the patients were diagnosed with non-ST elevated myocardial infarction (NSTEMI), 36.8% with ST elevated myocardial infarction (STEMI), 3.41% with unstable angina, 0.56% with stable angina, and 0.11% were diagnosed with various types of arrhythmias. The left anterior descending artery (LAD) was the most common culprit lesion in 51% of the patients. There were initially 65.2% of conservatively treated patients vs. 33.4% that underwent percutaneous coronary intervention (PCI) or 1.28% that underwent coronary artery bypass graft (CABG). SCAD-PCI revascularization was associated with a variable range of PCI failure. The most common complications were hematoma extension and iatrogenic dissection. SCAD-PCI revascularization frequently required three or more stents and had residual areas of dissection. The overall reported in-hospital and follow-up mortality rates were 1.2% and 1.3%, respectively. The follow-up range across studies was 7.3–75.6 months. The authors reported variable prevalence of MACE, recurrent SCAD up to 31%, ACS up to 27.4%, TVR up to 30%, repeat revascularization up to 14.7%, UA up to 13.3%, HF up to 17.4%, and stroke up to 3%. Conclusion Our results highlight that conservative treatment should be the preferred method of treatment in patients with SCAD. PCI revascularization is associated with a high prevalence of periprocedural complications. SCAD poses a considerable risk of MACE, mainly associated with TVR, ACS, and recurrent SCAD.